2022
DOI: 10.21603/2074-9414-2022-1-189-198
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electric Field Processing as an Effective Tomato Peeling Method

Abstract: Electrophysical technologies are a global trend of sustainable agriculture and food industry. Peeling is an energy-intensive procedure of fruit and vegetable processing. The research featured the effect of pulsed electric field (PEF) treatment on tomato peeling effectiveness. The assessment included such factors as specific effort, energy costs, and product losses in comparison with thermal and electrophysical methods. Tomatoes of Aurora variety underwent a PEF treatment at 1 kV/cm. The expended specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…The first 8 experiments were performed at noncenter points to obtain an overview, and the final 5 experiments were performed at the center points. During a pilot study of PEF application for peeling [18], two main factors were identified that affect the kiwifruit peeling performance: the time elapsed after PEF treatment before peeling (X 1 ) and the PEF-specific energy input (X 2 ).…”
Section: Experimental Design and Processmentioning
confidence: 99%
See 1 more Smart Citation
“…The first 8 experiments were performed at noncenter points to obtain an overview, and the final 5 experiments were performed at the center points. During a pilot study of PEF application for peeling [18], two main factors were identified that affect the kiwifruit peeling performance: the time elapsed after PEF treatment before peeling (X 1 ) and the PEF-specific energy input (X 2 ).…”
Section: Experimental Design and Processmentioning
confidence: 99%
“…Depending on the applied field strength, the pores can be reversible or irreversible. With regard to peeling, the benefits of PEF have already been observed for tomatoes [18]. In this study, the influence of different PEF treatment settings on the peeling of kiwifruit, as well as on the physicochemical parameters including pH, °Brix, water activity, phenolic compound, colour, and antioxidant capacity, was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The suggested CAP treatment can be potentially used as an alternative to traditional technologies such as chemical and thermal treatment. Khudyakov et al [31] compared the efficacy of peeling with pulsed electric field pretreatment (E = 1 kV/cm; specific energy 1, 5, and 10 kJ/kg) for the tomato peeling procedure. It was found that tomato peeling was more effective at 1 kJ/kg.…”
Section: Improvement In Peeling Of Whole Tomatomentioning
confidence: 99%